Post a New Question


posted by .

Find the indefinite integral.
(e^(4 x) + e^(-5 x)) dx

  • Math -

    recall that ∫ e^u du = e^u

    ∫e^(4x) dx
    let u = 4x, so du = 4 dx. That means that you have

    ∫e^(4x) (1/4)(4x dx) = ∫ 1/4 e^u du = 1/4 e^u = 1/4 (e^4x)

    similarly, for any constant a,

    ∫e^(ax) dx = 1/a e^(ax)

    and as always, don't forget the +C !

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question